2017
DOI: 10.1021/acsnano.6b08650
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis Reveals Similar Transcriptomic Responses to Intrinsic Properties of Carbon Nanomaterials in Vitro and in Vivo

Abstract: Understanding the complex molecular alterations related to engineered nanomaterial (ENM) exposure is essential for carrying out toxicity assessment. Current experimental paradigms rely on both in vitro and in vivo exposure setups that often are difficult to compare, resulting in questioning the real efficacy of cell models to mimic more complex exposure scenarios at the organism level. Here, we have systematically investigated transcriptomic responses of the THP-1 macrophage cell line and lung tissues of mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…For determination of gene expression profiles, mRNA isolation, quality control, amplification, hybridization, scanning, and data preprocessing/normalization were carried out for all 129 samples as described previously, with slight modifications. Briefly, raw data files were imported into R and preprocessed with the methods available in the Limma package .…”
Section: Methodsmentioning
confidence: 99%
“…For determination of gene expression profiles, mRNA isolation, quality control, amplification, hybridization, scanning, and data preprocessing/normalization were carried out for all 129 samples as described previously, with slight modifications. Briefly, raw data files were imported into R and preprocessed with the methods available in the Limma package .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, although most of the altered pathways that were identified are shared between the two experimental models, the specific genes that are involved are different (Poulsen et al, 2013). Moreover, although differences in gene expression exist between in vivo and in vitro exposure to CNT, in vitro exposures can efficiently recapitulate the significantly altered molecular functions in vivo (Kinaret et al, 2017).…”
Section: Studies In Rodentsmentioning
confidence: 99%
“…In addition to a variety of in vitro end point assessments, OMICS approaches allow for comparison of different in vitro systems as well as better correspondence to in vivo exposure scenarios (Kinaret et al, 2017b;Drasler et al, 2017). Combination of different OMICS methods can inform more thoroughly about ENMs MOA, which could be further used in ENM grouping approaches, as suggested by Riebeling et al (2017).…”
Section: Molecular Effectsmentioning
confidence: 99%
“…We and others already showed that ENMs are able to exert toxic effects on the respiratory system, by using animal exposure models (Kinaret et al, 2017a;Rydman et al, 2015;Rydman et al, 2014). Apart from the pathological responses, ENMs MOA has been investigated in different tissues (Kinaret et al, 2017b;Fröhlich, 2017;Costa and Fadeel, 2016), by analyzing the molecular perturbations that these materials are able to induce on the normal transcriptional program of exposed cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation